Fertility in Adult Bitches Previously Treated with a 4.7 mg Subcutaneous Deslorelin Implant. Issue 6 (8th October 2015) - Borges, P; Fontaine, E; Maenhoudt, C; Payan‐Carreira, R; Santos, N; Leblond, E; Fontaine, C; Fontbonne, A
Content: The absence of fertility problems in male dogs after a single treatment with deslorelin acetate (Suprelorin ® ) is well acknowledged. However, reports on the application of deslorelin in the bitch and information concerning fertility after implant treatment are still limited. In this retrospective study, data concerning induced and spontaneous oestruses of 39 bitches from 17 breeds, treated with deslorelin acetate implants (4.7 mg Suprelorin ®, Virbac, France), were retrieved to assess post‐treatment fertility (ovulation rate, pregnancy rate and litter size). Animals were grouped according to treatment characteristics: group 1 (Gr1) – females submitted to oestrus induction, showing natural oestruses afterwards (n = 19); group 2 (Gr2) – females re‐implanted with 4.7 mg deslorelin acetate to re‐induce oestrus, showing subsequent spontaneous post‐implant oestruses (n = 7); and group 3 (Gr3) – females submitted to a 4.7 mg deslorelin acetate implant for oestrus suppression, evaluated at subsequent spontaneous post‐implant oestruses (n = 13). Comparison of fertility traits between induced and post‐treatment spontaneous oestruses in Gr1 and Gr2 (short treatments), or between spontaneous oestruses after long‐treatment schedules (Gr 3) revealed a slightly better performance in spontaneous cycles compared with induced cycles: ovulation rate post‐treatment was 97.1%, 94.1% and 94.4% and the pregnancy rate post‐treatment was 91.2%, 88.9% and 84.6% for groups 1, 2 and 3, respectively. Nevertheless, fertility in induced and post‐treatment oestruses was considered normal. Moreover, the individual litter size did not differ within groups between induced and spontaneous cycles. From these findings, we concluded that treatment with 4.7 mg deslorelin implants did not compromise the bitches' fertility in subsequent oestruses.